A general equilibrium analysis of the impact of inward FDI in Ghana: The role of complementary policies - Lawrence Arbenser (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2004)
The need for external capital (FDI) inflow to finance the current account deficit of developing countries cannot be over-emphasized. Foreign direct investment takes predominance over other types of capital inflow into developing countries. How would an increase in FDI and a reduction in import tariff levels in isolation affect household welfare and other macroeconomic indicators? How would the concurrent application of the two enhance the expected impact? This paper explores the above questions by using a Computable General Equilibrium (CGE) model for Ghana, implemented in the General Algebraic Modeling System (GAMS) to carry out specific counter factual simulations. This paper concludes that the primary benefit of an increase in FDI inflow for a developing economy is the increase in current consumption. It also establishes that policies which ensure increase in FDI inflow and reduce tariff levels are complementary policies that enhance household welfare. It also emphasizes that the two policies will have different impact on macroeconomic indicators, inter alia exchange rate, export, import and trade deficit.
Keywords: 330; FDI; Import tariff; CGE; Ghana; GAMS; house hold welfare trade deficit; exchange rate; import; export